The Evolution and Growth of Nearby Galaxy Groups - Fosdick, Katiya Claire (Proceedings of the Wisconsin Space Conference, 2022)
<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">This project strives to study the relationship between the group environment and individual galaxy properties. Group richness is used as a proxy for different environmental conditions and mass to form a sample of 40 low mass (<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">3<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">N<10<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">), 40 medium mass (<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">10<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">N<20<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">), and 40 high mass (<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">20<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">N<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">) groups from the Berlind et al. 2006 volume-limited Mr18 catalog and Tempel et al. 2014 flux-limited catalog. Unique Color-Magnitude-Position and Color-Stellar Mass-Position diagrams are produced for each sample group. I identified dynamically active and inactive groups using the magnitude gap through a crude version of methodology described in Raouf et al. 2019. Project figures are used to analyze how BGG properties, dynamic activity, and group appearance depend on group richness. Analysis focuses on BGGs to understand how one evolutionary mechanism, mergers, is impacted by basic differences in a group’s environment.